Pengaruh Penyuluhan Dampak Kebiasaan Buruk terhadap Susunan Gigi serta Kebersihan Gigi dan Mulut pada Komunitas Orang Tua TK Al Hidayah II, Kelapa Gading - Olivia Nauli Komala; Dewi Lilyani Margaretha; Ferry Sandra; Johan Arief Budiman (JURNAL ABDIMAS KESEHATAN TERPADU, 2022)
Caries, periodontal disease, and malocclusion are the most common problems. The cause can be in the form of habits such as the technique and timing of brushing teeth that are not good and correct, the habit of sucking lips or fingers, biting nails, breathing through the mouth, and grinding teeth. These habits are still experienced by some students of TK Al-Hidayah 2 who are participants of this activity. As many as 21.62% of parents have less knowledge and 24.32% of parents have sufficient knowledge about dental and oral health and habits that can affect it. Extension activities are carried out by providing material and conducting questions and answers with parents of students and providing goodie bags. Posttest was also conducted to find out feedback from students on the material provided. The results of training counseling on maintaining oral health for parents and teachers at Alhidayah 2 Kindergarten, Kelapa Gading. conducted through the media webinars showed satisfactory results. There is an increase in the mean of 1 correct answer from pre-test to post-test which is statistically significant (t-count>t-table).